Untold Stories of Teachers and Graduates of Alternative Learning Systems - Pimienta-Mendoza, Dhean Jencel (Journal of Interdisciplinary Perspectives, 2024)
The study aimed to determine the experiential accounts of Alternative Learning System teachers and graduates and the relationship between their experiences in the 1st District of Ilocos Sur. It utilized the transcendental phenomenological research applying the focus group discussion and a reviewed semi structured open-ended question. Participants' responses were recorded and transcribed verbatim, listed, categorized, coded, and thematized using the Moustakas framework. Teachers and graduates of Alternative Learning System share a unique relationship characterized by equal efforts to achieve a common goal and built on mutual respect, trust, and understanding. In conclusion, the relationship between teachers and graduates is crucial to the program's success. The equal efforts of both parties have resulted in the empowerment of individuals who have not been able to complete their basic education through traditional means. It is important to recognize the role of teachers in the lives of graduates and provide them with the necessary support and resources to continue their work. In this way, Alternative Learning System programs can continue to make a positive impact on the lives of those seeking to improve their lives through education.